Molecular regulation of cork development: the QsMYB1 gene - Almeida, Tânia Raquel Domingues (2018)
Cork is a natural and renewable material obtained as a sustainable product from cork oak (Quercus suber L.) during the tree’s life. Cork formation is a secondary growth derived process resulting from the activity of cork cambium. However, despite its economic importance, only very limited knowledge is available about the molecular mechanisms underlying the regulation of cork biosynthesis and differentiation. The work of this PhD thesis was focused on the characterization of an R2R3-MYB transcription factor, the QsMYB1, previously identified as being putatively involved in the regulatory network of cork development. The first chapter introduces cork oak and secondary growth, with special emphasis on cork biosynthesis. Some findings concerning transcriptional regulation of secondary growth are also described. The MYB superfamily and the R2R3-MYB family (in particular) of transcription factors are introduced. Chapter II presents the complete QsMYB1 gene structure with the identification of two alternative splicing variants. Moreover, the results of QsMYB1 expression analysis, done by real-time PCR, in several organs and tissues of cork oak are also reported. Chapter III is dedicate to study the influence of abiotic stresses (drought and high temperature) and recovery on QsMYB1 expression levels. The effects of exogenous application of phytohormones on the expression profile of QsMYB1 gene are evaluated on Chapter IV. Chapter V describes the reverse genetic approach to obtain transgenic lines of Populus tremula L. x tremulóides Michx. overexpressing the QsMYB1 gene. Finally, in Chapter VI the final conclusions of this PhD thesis are presented and some future research directions are pointed based on the obtained results.